2016
DOI: 10.1590/0102-3772e322211
|View full text |Cite
|
Sign up to set email alerts
|

Validação do Questionário de Avaliação de Habilidades Sociais, Comportamentos, Contextos para Universitários

Abstract: RESUMO -Verifica-se uma carência de instrumentos que avaliem habilidades sociais na interface com a saúde mental de universitários. Objetiva-se testar as propriedades psicométricas de validade e fidedignidade do Questionário de Avaliação de Habilidades Sociais, Comportamentos e Contextos para Universitários -QHC-Universitários. Procedeu-se à avaliação, em situação coletiva, de 609 estudantes universitários de diferentes cursos por meio dos seguintes instrumentos: QHC-Universitários, IHS-Del Prette, BDI, Mini-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
0
2
0
4
Order By: Relevance
“…For the process of cross-cultural adaptation, referent to Stages 1, 2, 3 and 4, the research team, along with the judges, made the relevant adaptations in a qualitative way, in line with the procedures indicated in the literature for this process (Pasquali, 2010;Sampieri et al, 2013). These analyses have also been undertaken in other studies with this purpose (Bolsoni-Silva & Loureiro, 2016;Gomes & Boruchovitch, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For the process of cross-cultural adaptation, referent to Stages 1, 2, 3 and 4, the research team, along with the judges, made the relevant adaptations in a qualitative way, in line with the procedures indicated in the literature for this process (Pasquali, 2010;Sampieri et al, 2013). These analyses have also been undertaken in other studies with this purpose (Bolsoni-Silva & Loureiro, 2016;Gomes & Boruchovitch, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nesta categoria foram agrupados os quatro estudos com foco principal na avaliação e validação de instrumentos de avaliação de HS. Três deles utilizaram o IHS-Del-Prette, dois como medida de referência para verificar a validade de um novo instrumento 27,28 O estudo 1 desta categoria 27 analisou a validade do Questionário de Avaliação de Comportamentos e Contextos para Universitários (QHC-Universitários) e constatou correlação positiva moderada (r=0,498; p=0,001) entre o escore total do IHS-Del--Prette e o indicador "Falar em Público" e correlação negativa moderada (r=0,475; p=0,003) com o indicador "Dificuldades" do QHC. Em relação às propriedades psicométricas, o QHC apresentou alfas de Cronbach de 0,657 tanto na parte 1 quanto na parte 2, sendo este considerado um valor aceitável para consistência interna.…”
Section: Instrumentos De Avaliação De Habilidades Sociaisunclassified
“…It is worth noting that the positive results in the professionals' behavioral evaluations after training become positive impacts on these participants. In such context, a survey that assessed social skills, behaviors, and contexts for college students noted that most participants could identify difficulties in behaviors that are components of factors such as expressing negative feelings, opinions, and dealing with criticism; and indicated that the evaluation is more accurate when assessing the frequency and quality with which the behaviors are emitted, in face of different situations and interlocutors (24) .…”
Section: Assessment Of Self-reported Behavior By the Nursing Teammentioning
confidence: 99%